Clinical utility of NGS diagnosis and disease stratification in a multiethnic primary ciliary dyskinesia cohort. Issue 5 (25th December 2019) - Fassad, Mahmoud R.; Patel, Mitali P.; Shoemark, Amelia; Cullup, Thomas; Hayward, Jane; Dixon, Mellisa; Rogers, Andrew V.; Ollosson, Sarah; Jackson, Claire; Goggin, Patricia; Hirst, Robert A.; Rutman, Andrew; et al.
Abstract : Background: Primary ciliary dyskinesia (PCD), a genetically heterogeneous condition enriched in some consanguineous populations, results from recessive mutations affecting cilia biogenesis and motility. Currently, diagnosis requires multiple expert tests. Methods: The diagnostic utility of multigene panel next-generation sequencing (NGS) was evaluated in 161 unrelated families from multiple population ancestries. Results: Most (82%) families had affected individuals with biallelic or hemizygous (75%) or single (7%) pathogenic causal alleles in known PCD genes. Loss-of-function alleles dominate (73% frameshift, stop-gain, splice site), most (58%) being homozygous, even in non-consanguineous families. Although 57% (88) of the total 155 diagnostic disease variants were novel, recurrent mutations and mutated genes were detected. These differed markedly between white European (52% of families carry DNAH5 or DNAH11 mutations), Arab (42% of families carry CCDC39 or CCDC40 mutations) and South Asian (single LRRC6 or CCDC103 mutations carried in 36% of families) patients, revealing a striking genetic stratification according to population of origin in PCD. Genetics facilitated successful diagnosis of 81% of families with normal or inconclusive ultrastructure and 67% missing prior ultrastructure results. Conclusions: This study shows the added value of high-throughput targeted NGS in expediting PCD diagnosis. Therefore, there is potential significant patient benefit in wider and/or earlier implementation of genetic screening.